Single Mothers of Nairobi: Rural-Urban Migration and the Transformation of Gender Roles and Family Relations in Kenya - Meda, Stefania Giada (Lidé města, 2013)
The paper delineates the changes in gender roles and family relations brought about by rural-urban migration in Kenya by discussing the findings of empirical qualitative research carried out in Kenya in September 2011 on the single mothers of Nairobi, an emerging family form in Kenyan society, widespread yet unspoken and still in search for recognition. The theoretical framework makes reference to the relational sociology and takes into account how the family stakeholders relate to one another and how changes in reciprocal relations (i.e., inter-gender relations) may produce further changes in the whole family. The idea is to show how the emergence of this new form of family is: i) strongly linked to the migration from the countryside to the city of Nairobi and the cultural and social transition that this brings about (a transition from tradition to modernity); and to cast light on ii) the characteristics of the new role played by women within their families and the communities; iii) elements of novelty and discontinuity compared to the tradition; iv) challenges and resources of the single mothers. Various tools of investigation were used (participant observation, structured data sheets, in-depth interviews, semi-structured individual interviews, group interviews, individual structured questionnaires) on a number of Nairobi single mothers and key informants.